Powered Tool for the Removal of a Well-Fixed Acetabular Cup: A Comparative Experimental Study - Chung, Jun Young; Cha, Yonghan; Jung, Chang Ho; Kim, Jin Woo; Yoo, Jun Il; Kim, Jung Taek; Jeon, Yongho (CiOS Clinics in Orthopedic Surgery, 2025)
Background: The removal of a well-fixed acetabular cup is a challenging, labor-intensive, and time-consuming step during revision hip arthroplasty. Although the advent of the manual osteotome, Explant, has simplified the procedure, it is still a stressful process as it dissipates the surgeon’s strength and time and risks an iatrogenic pelvic fracture. Recently, EZX, a powered tool for extraction of well-fixed acetabular cups with semicircular blade was invented. This study aimed to compare Explant and EZX in an experimental condition for their efficacy and safety. Methods: Cementless acetabular cups were press-fitted to 20 hemipelvic polyurethane models using foam adhesives. Ten cups were removed with each tool for comparison of the elapsed time, loads on the entire hemipelvis, periacetabular strain and tem-perature, volume of periacetabular bone removed, and diameter of the remaining acetabular rim. Strains and loads were quantitatively assessed using strain gauges and load cells for precise and reliable measurements. Results: The mean duration required to remove a well-fixed cup with EZX was 38.5 seconds (range, 25–55), whereas that with Explant was 543.7 seconds (range, 214–1,051) (p < 0.001). The load on the entire hemipelvis with EZX (mean, 9.1 kgf; range, 6.4–11.3) was 33% lower than that with Explant (mean, 13.6 kgf; range, 9.2–17.1) (p < 0.001). The periacetabular peak strains at the 3 positions with EZX were significantly lower than those with Explant (p < 0.001). The temperature during the removal did not differ significantly between the 2 tools. Although the mean volume of bone loss with Explant was 2.4 mL more than that with EZX (p < 0.001), the mean diameters of the remaining acetabular rim were not significantly different, measuring 54.1 mm with both tools. Conclusions: The present experiment revealed that a well-fixed cup could be removed using a powered tool with less strength and time and less load on the entire pelvis. Although the powered tool removed a larger volume of bone, the diameters of the remaining acetabular rims were equivalent. This tool may help surgeons remove well-fixed cups in a short time and reduce the de-forming load on the bone around the cup without increasing the size of the subsequent reconstruction cup.
Keywords: Acetabulum; Arthroplasty; Hip; Orthopedic equipment; Prosthesis failure; Replacement